Non-genomic actions of thyroid hormones regulate the growth and angiogenesis of T cell lymphomas - Cayrol, María Florencia (2019)
Fil: Cayrol, María Florencia. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina